2021
DOI: 10.1186/s43094-020-00160-9
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bioactive compounds from Euphorbia cotinifolia

Abstract: Background Green plants are found to be an effective reservoir for bioactive molecules and can provide appreciable sources of antimicrobial agents. Antibacterial activity of solvent extracts of Euphorbia cotinifolia leaves was tested by agar cup diffusion and broth microdilution methods against some common human pathogenic bacteria viz., Bacillus cereus, Klebsiella pneumonia, Enterobacter aerogenes, Escherichia coli, Staphylococcus aureus, Bacillus subtilis, and Salmonella typhi. The methanol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The antimicrobial efficacy of different Euphorbia species is well documented in previous studies [ 38 , 64 , 65 , 66 , 67 ]. Previously, Li et al [ 68 ] have reported the isolation of three antibacterial ent-abietane-type diterpenoids from the root extract E. wallichii .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The antimicrobial efficacy of different Euphorbia species is well documented in previous studies [ 38 , 64 , 65 , 66 , 67 ]. Previously, Li et al [ 68 ] have reported the isolation of three antibacterial ent-abietane-type diterpenoids from the root extract E. wallichii .…”
Section: Discussionmentioning
confidence: 77%
“…Previously, Li et al [ 68 ] have reported the isolation of three antibacterial ent-abietane-type diterpenoids from the root extract E. wallichii . However, Jayalakshmi et al [ 65 ] have attributed the antibacterial activity of Euphorbia cotinifolia to phenols and flavonoids. In the current study, higher concentrations (1000 µg/mL and 500 µg/mL) of aqueous leaf extract showed comparable antibacterial activity, which was reduced significantly in response to lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…For E. coli , the methanol solvent demonstrated a higher antibacterial activity than other solvents; however, it presented a little higher zone of inhibition on E. coli than the ethanol solvent. EPB presented a higher zone of inhibition on E. coli than other studies except the study of Jayalakshmi B. et al , 61 whereas PBB demonstrated a higher or closer zone of inhibition on E. coli than other studies except the studies of Jayalakshmi B. et al , Valle D. L. et al , and Kulnanan P. et al 16,61,62 . Finally, since methanol is known as a more toxic solvent than ethanol, ethanol might be suitable for use as the extraction solvent of P. betle for the antibacterial activities on both S. aureus and E. coli more than methanol.…”
Section: Resultsmentioning
confidence: 66%
“…Plants derived natural products are a rich source of chemically and functionally diversified compounds and provide remarkable assistance in drug development programs. [1] Medicinal plants are being used in multiple traditional, conventional and complementary systems especially for the treatment of cancer. The bioactive compounds isolated from medicinal plants have been proven safe and effective for the treatment of multiple types of cancers.. [2] Flavonoids are among the extensively distributed class of secondary metabolites exhibiting numerous therapeutic activities such as anti-oxidant, anti-cancer, antiviral, anti-allergic and anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…Plants derived natural products are a rich source of chemically and functionally diversified compounds and provide remarkable assistance in drug development programs [1] . Medicinal plants are being used in multiple traditional, conventional and complementary systems especially for the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%